2018
DOI: 10.19150/me.7978
|View full text |Cite
|
Sign up to set email alerts
|

Open-air sprays for capturing and controlling airborne float coal dust on longwall faces

Abstract: Float dust deposits in coal mine return airways pose a risk in the event of a methane ignition. Controlling airborne dust prior to deposition in the return would make current rock dusting practices more effective and reduce the risk of coal-dust-fueled explosions. The goal of this U.S. National Institute for Occupational Safety and Health study is to determine the potential of open-air water sprays to reduce concentrations of airborne float coal dust, smaller than 75 µm in diameter, in longwall face airstreams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…The spray characterization study also measured an unconfined spray dust capture efficiency on respirable coal dust of approximately 21%. A later study found the same full cone spray achieved a 40% KE for FCD when operating in an unconfined space at 1103 kPa [ 14 ]. The full cone spray achieved the highest KE of all sprays tested and does not have a preferential orientation, which is why it was selected for use in the water curtain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The spray characterization study also measured an unconfined spray dust capture efficiency on respirable coal dust of approximately 21%. A later study found the same full cone spray achieved a 40% KE for FCD when operating in an unconfined space at 1103 kPa [ 14 ]. The full cone spray achieved the highest KE of all sprays tested and does not have a preferential orientation, which is why it was selected for use in the water curtain.…”
Section: Discussionmentioning
confidence: 99%
“…Full cone sprays (SpiralJet Nozzle No. 1/4GG3, Spraying Systems Co., Wheaton, IL) were selected for use in this study because they provided maximum knockdown during single spray tests and also have no preferential orientation [ 14 , 15 ]. The operating pressure of the spray bar was maintained at 1103 kPa, which consumes approximately 3.8 lpm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Untuk menahan partikel bermuatan agar kecepatan rata-rata tetap digunakan kecepatan hanyut. Kecepatan hanyut (243)(244)(245)(246)(247) mempunyai arah sama dengan medan listrik dan hubungan keduanya dinyatakan dalam suatu konstanta yang disebut dengan mobilitas.…”
Section: Kecepatan Hanyutunclassified
“…Studies have shown differences in airborne respirable dust removal rates for various spray nozzle designs (Pollack and Organiscak 2007;Beck et al 2018). Pollock and Organiscak (2007 found that spray nozzle designs with wider nozzle angles reduce water droplet sizes and droplet velocities, but induce more air flow.…”
Section: A11mentioning
confidence: 99%